Numerical solution of differential-algebraic equations with index-2 - Guzel, N; Bayram, M (ELSEVIER SCIENCE INC, 2006)
In this paper, numerical solution of differential-algebraic equations (DAEs) with index-2 has been presented using Pade approximation method. An index reduction for differential-algebraic equation with index-2 is suggested. First index-2 system is reduced to index-1 system. Then we have applied the method for solving differential-algebraic equations with index-2, numerically. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: differential-algebraic equations (DAEs); index-2; Pade approximation; Mathematics